Plan de negocios para la comercializadora de autopartes, "cabinas y repuestos" en Bogotá (2017)
This work begins with a description of the heavy and semi-heavy land transport sector in the 2005-2015 period, showing the importance it has had for the development of the country, as well as the contribution to the gross domestic product, besides analyzing different factors as the number of freight vehicles in the national territory, focusing the investigation on the analysis of the factors that determine the demand of the autoparts market.